Variabilidade espaço-temporal da comunidade de macroinvertebrados bentônicos na microbacia do Rio Lontra na região Sudoeste do Estado do Paraná. - Bazilio, Sérgio (2015)
Benthic macroinvertebrate community is very important to streams, since they make part of the energy flow and are also an important food source for adjacent and upper trophic levels. They form a very diversified fauna and their structure may be influenced by several environmental factors, which vary in time, space and in an analyzed scale. Samples were taken from benthic macroinvertebrates and environmental descriptors during winter, spring and summer of 2012 and autumn of 2013 in ten sampling points in Lontra river watershed (Paraná, Brazil). Thus, this study aimed at: a) characterizing the watershed morphometry in Lontra river with data from the Shuttle Radar Topography Mission (SRTM); b) analyzing the structure of benthic macroinvertebrate community according to their taxonomic family level and functional groups; c) investigating seasonal variation (during the four seasons) and spatial variation of this community structure due to spatial differences in morphological and physiographic characteristics of the sampled sections; d) identifying the community variability of benthic macroinvertebrates at three spatial scales (river, river segment and mesohabitat) emphasizing spatial scales, which best explain the community structure in this watershed; e) investigating which measured environmental descriptors influence on the community structure and f) which variability percentage in organisms richness can be explained by the measured local environmental descriptors.